Analysis of VFDPC for three-level neutral point clamped AC-DC converters with capacitor balancing solution - Razali, Azziddin Mohamad; Mohd Yusoff, Nor Azizah; Ab Shukor, Syahar Azalia; Mohamed Hariri, Muhammad Hafeez; Jidin, Auzani; Sutikno, Tole (Indonesian Journal of Electrical Engineering and Computer Science, 2025)
This paper presents an analysis of the dynamic performance of a three-level neutral point clamped (NPC) AC-DC converter utilizing the advanced control technique of virtual flux direct power control (VFDPC). VFDPC estimates the three-phase grid voltage and instantaneous active and reactive power components, eliminating the need for an AC input voltage sensor used in conventional direct power control (DPC). This reduction in sensors decreases system complexity and cost while mitigating high-frequency noise and interference. Integrating VFDPC into 3L NPC AC-DC converters significantly enhances overall performance, leading to more efficient and robust power conversion systems. However, a significant challenge in the three-level NPC topology is the voltage imbalance in the neutral point of the DC-link capacitor, which can cause excessive voltage stress on switching devices and degrade system performance. To address this, a novel lookup table has been developed, incorporating strategies to balance the capacitor voltage. The results of this study demonstrate that VFDPC generates nearly sinusoidal line currents with reduced current total harmonic distortion (THD). Additionally, VFDPC ensures unity, lagging, and leading power factor operation, while providing flexibility to adjust the DC-link output voltage and accommodate load variations. These capabilities highlight VFDPC effectiveness in managing power quality and system stability, even under varying load conditions.